Wired and dangerous : how your customers have changed and what to do about it - Bell, Chip R.; Patterson, John R. (John Rice), 1951- (San Francisco : Berrett-Koehler Publishers, 2011)
Customers today are picky, fickle, and vocal, and all about me vain. They now have an enormous variety of services and products to choose from, with unprecedented access to information and reviews.
Includes bibliographical references (p. 233-235) and index.
Keywords: Customer relations; Customer services; Customer loyalty; Internet